Alliance negotiation as a predictor of early treatment outcome - Manubens, Rocío Tamara (2023)
Aim: The therapeutic alliance is a robust predictor of treatment outcome. However, little is known about the way alliance negotiation contributes to psychotherapy outcome. The aim of the present study was to analyze the effects of alliance negotiation on treatment outcome in the first four sessions of psychotherapy. Methods: Ninety-six patients diagnosed with emotional disorders received weekly Solution-Focused Brief Therapy. Each patient completed both the Alliance Negotiation Scale (ANS) and the Outcome Questionnaire 45 (OQ.45) after each of the first four sessions. Both between- and within-patients effects of alliance negotiation on symptom severity were analyzed using Hierarchical Linear Models. Results: Results showed significant between and within patient effects of alliance negotiation on symptom severity. Patients with higher levels of alliance negotiation across treatment showed lower levels of symptom severity (between-patient effect). Also, in a session with higher alliance negotiation compared to the average session of this patient, symptom severity was lower than in the average session (within-patient effect). Discussion: The results indicate that therapies characterized by higher alliance negotiation and sessions with higher alliance negotiation are beneficial for early outcome. Conclusion: From a clinical point of view, the results suggest that alliance negotiation is a meaningful factor for therapy outcome and that therapists may benefit from training and monitoring alliance negotiation during the early stages of treatment.